Assistant programming software: a new tool for an improved programming of pacemakers. - Lascault G; Nitzsché R; Ritter P; Remy M; Limousin M (Pacing & Clinical Electrophysiology, 1990)
Programming the new DDD pacemakers is becoming increasingly difficult. One must take into account the pacemaker's complexity, the fact that some parameters are linked to others, and the clinical profile of the patient. This difficult problem will lead to the design of software to assist programming, which will help the implanting physicians in choosing adequate programmed settings adapted to the functioning of the device and to the physiology and pathology of the patient. These programming aides should meet certain basic requirements to make them safe, efficient, and easy to use. One such system designed by ELA Medical, 'Programming Assistant' is herein described. The preliminary results of an initial study on the acceptance of this programming aide among physicians involved in cardiac pacing are given and discussed.